(untitled) (Research, Society and Development, 2025)
The ornamentation of environments with bioactive species promotes collaborative landscaping, preserving the plant heritage while beautifying it. These species have multifunctional aptitudes, allowing the user to benefit from both food and ornamental purposes. Thus, the objective of this work was to carry out a floristic survey of bioactive species in the multipurpose space of the Horto Mandala, with potential for use in landscaping. The aim was to utilize them functionally, from ornamentation to the preservation of regional biodiversity. The survey was conducted through analysis of the ecophysiological and aesthetic characteristics of plants to verify their ornamental potential, through in situ observations in the multipurpose space of the Horto Mandala. The presence of 43 plant species was observed, distributed in 14 botanical families, most of exotic origin, all with an annual cultivation cycle and potential for ornamental use. It is concluded that the multipurpose space is well cared for and the maintenance of the species is in good condition in terms of phytosanitary aspects and typical formation. The number of species present in this area allows for the diversity of the place, in addition to its beautification through the variety of colors of the leaves and flowers.